Gen-z consumer behavior in the cosmetics industry: analyzing the impact of shopping patterns, pricing strategies, and emotional drivers on unplanned purchases - Jannah, Zahratul; Maulana, Arief (Universitas Negeri Padang, 2024)
This study aims to analyze the effects of Shopping Lifestyle, Price Discount, and Hedonic Shopping Motivation on Impulse Buying among Gen-Z customers of Somethinc brand cosmetics in Padang City. The research employs a quantitative method with a causative approach to examine the relationships and influences between variables. Data were collected through questionnaires distributed to 111 respondents who met specific criteria, including customers who had made impulse purchases of Somethinc products and were aware of the product promotion program. The results reveal that Shopping Lifestyle and Hedonic Shopping Motivation have significant influences on Impulse Buying, while Price Discount does not demonstrate a significant impact. The regression coefficient for Shopping Lifestyle is 0.448 (p < 0.05) and for Hedonic Shopping Motivation is 0.254 (p < 0.05), indicating that these two variables positively influence impulse buying behavior. In contrast, Price Discount, with a coefficient of 0.026 (p > 0.05), does not significantly influence impulse buying decisions.